1999
DOI: 10.1515/bc.1999.152
|View full text |Cite
|
Sign up to set email alerts
|

SHP1 Protein Tyrosine Phosphatase Negatively Modulates Erythroid Differentiation and Suppression of Apoptosis in J2E Erythroleukemic Cells

Abstract: The SH2 domain-containing tyrosine phosphatase SHP1 is known to play a crucial role in the regulation of hematopoiesis. It has been shown previously that SHP1 associates with the activated erythropoietin receptor (EPOR) and negatively regulates mitogenic signaling. To further elucidate the role of SHP1 in erythropoietin (EPO)-induced cellular responses we employed J2E erythroleukemic cells as a model for erythroid maturation and cytokine-triggered suppression of apoptosis. Our data indicate that overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…Inspection of quadrant eight reveals that the point mutant preferentially activates proteins involved in immune system signaling. For example, Tec and Shp1 are both critical mediators of normal hematopoiesis [27,28] and, when dysregulated, may contribute to leukemogenesis [29,30]. These and other proteins listed in 1432 ZHANG ET AL.…”
Section: Quantitative Phosphoproteomic Analysis Of Flt-3 Signaling Inmentioning
confidence: 99%
“…Inspection of quadrant eight reveals that the point mutant preferentially activates proteins involved in immune system signaling. For example, Tec and Shp1 are both critical mediators of normal hematopoiesis [27,28] and, when dysregulated, may contribute to leukemogenesis [29,30]. These and other proteins listed in 1432 ZHANG ET AL.…”
Section: Quantitative Phosphoproteomic Analysis Of Flt-3 Signaling Inmentioning
confidence: 99%
“…Similarly, PTPeC, has been shown to inhibit JAK kinase phosphorylation resulting in inhibition of di erentiation and apoptosis in M1 cells stimulated by IL-6 and LIF (Tanuma et al, 2000). Bittorf et al (1999) recently showed that SHP1 inhibited erythropoietin-induced erythroid di erentiation and inhibition of apoptosis in an erythroleukemic cell line. This e ect of SHP1 was a result of inhibition of both the JAK kinase and MAP kinase pathways.…”
Section: Negative Regulation By Protein Tyrosine Phosphatasesmentioning
confidence: 99%
“…Similarly, PTPeC, has been shown to inhibit JAK kinase phosphorylation resulting in inhibition of dierentiation and apoptosis in M1 cells stimulated by IL-6 and LIF (Tanuma et al, 2000). Bittorf et al (1999) recently showed that SHP1 inhibited erythropoietin-induced erythroid dierentiation and inhibition of apoptosis in an erythroleukemic cell line. This eect of SHP1 was a result of inhibition of both the JAK kinase and MAP kinase pathways.…”
Section: Negative Regulation By Protein Tyrosine Phosphatases (Ptps)mentioning
confidence: 99%